Efektivitas Penggunaan Media Pembelajaran Bentuk Komik Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD Negeri 101822 Pancurbatu - Thessa Herdyana (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This study aims to determine the effectiveness of thematic learning media in the form of comics. So that it can help student learning outcomes. This research was conducted in grade IV Elementary School 101822 Pancurbatu. This study uses a quantitative approach. This research method is a quasi experiment with the design Nonequivalent Control Group Design. The population in this study was grade IV Elementary School 101822 Pancurbatu. The technique for determining the sample is custer sampling, namely class IVA as the experimental class and class IVB as the control class. The validity used was content validity and reliability using Cronbach's Alpha. The analysis technique used the t-test. The effectiveness test based on the gainc score in the experimental class obtained a value of 0.6255 in the moderate category. Meanwhile, the control class obtained an average valz ue of 0.2257 Gain Score in the low category. The pretest score of students in the experimental class before using thematic comics an average of 61.50. Meanwhile, the posttest scores of students after using thematic comics were an average of 87.00. The student's pretest score in the control class was 65.00 while the posttest score in the control class was 74.50. The results showed that the two posttest data on student learning outcomes had a value of t (= 0.000) so there was a difference because sig (2-tailed) <0.05 and tcount was positive so that H0 was rejected. This shows that the use of comics is very effective in improving learning outcomes